What Potential Benefits Do Village Renewal Programs Offer for Inner-Village Development in the Federal States Hessen, Mecklenburg-Western Pomerania, Lower Saxony, North Rhine Westphalia and Schleswig-Holstein? - Peter, Heike; Fengler, Birgit; Moser, Andrea (Raumforschung und Raumordnung | Spatial Research and Planning, 2013)
Against the background of demographic changes, the inner development of villages faces new challenges. This paper addresses the question of the potential benefits of village renewal programs for inner-village issues in the federal states Hessen, Mecklenburg-Western Pomerania, Lower Saxony, North Rhine Westphalia and Schleswig-Holstein and considers the impact of the specifically tailored individual state measures. To answer these research questions, regulatory documents will be illuminated, support data from years 2007 until 2009 will be assessed, and the results of an in-depth study of selected villages (village study) will be presented. The strategic direction of the responsible ministries is well-advanced on the state level and local actors are already sensitive to the urgency of the topic. However, the emphasis of village renewal programs continues to remain on the structural development of the villages. Support for social and functional development does take place, but must be intensified with a view toward sustainable inner-village development.
Keywords: Demographic changes; Inner-village development; Village renewal; Public support; Rural development